The Perspective of Maqashid Al-Sharia Theory in the Formulation of DSN Fatwas on Stocks - Cholili, Azwar; Muslih, Imam; Maghfiroh, Anisatul; Muttaqin, Muh. Syaukin; Yasid, Abu (Islamic Micro Finance Journal, 2024)
The capital market, as an innovation product that is an important tool in contemporary economic life, can bring the economy towards implementing Sharia principles and goals in the economic field. With the emergence of the Jakarta Islamic Index (JII), the differences between conventional and sharia capital markets are increasingly visible. By making JII a place to sell Sharia shares, customers can consider whether the Sharia capital market only depends on whether the shares being traded are halal or haram. In addition, there is a need for legal clarification regarding the actions of market players and the differences that exist between investors and speculators. Principles and objectives of Sharia economics. Utilizing the capital market to achieve beneficial objectives according to Islamic economic principles does not necessarily mean complying with Sharia